How important is career information and advice? - Sandra McNally (IZA World of Labor, 2016)
The quantity and quality of educational investment matter for labor market outcomes such as earnings and employment. Yet, not everyone knows this, and navigating the education system can be extremely complex both for students and their parents. A growing economic literature has begun to test whether interventions designed to improve information about the costs and benefits of education and application processes have an effect on students' behavior. So far, findings have been mixed, although the positive findings arising from some very carefully targeted interventions give cause for hope.
Keywords: I20; J24; 330; information interventions; randomized control trials; education decisions